Observational cohort study to investigate the unmet need and time waiting for referral for specialist opinion in adult asthma in England (UNTWIST asthma) - John D Blakey; Alicia Gayle; Mariel G Slater; Gareth H Jones; Michael Baldwin (BMJ Open)
Objectives This study aimed to estimate how many patients with asthma in England met the referral eligibility criteria using national asthma guidelines, identify what proportion were referred and determine the average waiting time to referral.Design This is an observational cohort study.Setting/Data sources Routinely collected healthcare data were provided by Clinical Practice Research Datalink records and Hospital Episode Statistics records from January 2007 to December 2015.Participants Patients with asthma aged 18–80 years participated in this study.Main outcome measures Eligibility for referral by the British Thoracic Society/Scottish Intercollegiate Guidelines Network (BTS/SIGN) 2016 guidelines, determined after a 3-month pharmacological therapy exposure assessment, was classed by either ‘high-dose therapies’, ‘continuous or frequent use of oral steroids’ or ‘incident eligibility’ during follow-up (continuous oral corticosteroids for more than 3 months, or ≥800 µg/day inhaled corticosteroids/long-acting β2-agonist (or three controllers) and ≥2 asthma attacks/year).Results From the final cohort (n=23293), 19837 patients were eligible for specialist referral during follow-up based on the BTS/SIGN guideline recommendations. Among eligible patients without any previously recorded referral, 4% were referred during follow-up, with a median waiting time of 880 days (IQR=1428 days) between eligibility and referral.Conclusions A large number of patients with asthma were eligible for specialist referral, of which a small proportion were referred, and many experienced a long waiting time before referral. The results indicate a major unmet need in asthma referral, which is a potential source of preventable harm and are likely to have implications regarding how services are organised to address this unmet need.